THE FREE MOVEMENT OF GOODS IN THE EUROPEAN UNION AND THE LIMITATION OF RENEWABLE PROMOTION SCHEMES TO THE MEMBER STATES OWN TERRITORY. - Diniz Araujo, Luiz Eduardo (REVISTA DA AGU, 2017)
This paper sets out to examine whether the legal framework of the European Union allows the Member States to design and apply renewables support schemes limited to their own territory, with a direct exclusion of the renewables energy produced in other Member States. The Directive 2009/28/EC will be interpreted at the light of the principle of free movement of goods inserted in the articles 34 and 36 of the Treaty on the Functioning of the European Union.